Articulatory distortions when using different types of mouthguard - Kia, Amy Cheen Liew; Dalia Abdullah,; Ter, Karyn Zuhuan; Puah, Shirley; Chan, Hui Yee; Soo, Eason; Badrulzaman Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A non-randomised controlled trial was conducted to compare the articulatory distortions of plosive sounds when using different types of mouthguards. Female national rugby players aged 18 and above were recruited, all of whom were native speakers of Malay without speech or hearing impairment. Boil-and-bite and custom-fitted mouthguards were provided for each participant. The articulation of phonemes with plosive sounds (/p/, /b/, /d/ and /t/) was recorded in a quiet room for the following conditions in a predetermined sequence: not using a mouthguard, using a boil-andbite mouthguard, and using a custom-fitted mouthguard. A washout interval of one hour was implemented among the conditions. The recorded speech waveforms were digitised and transcribed into the Praat software version 6.0.39 for spectrographic analysis. The mean voice onset time (VOT) for all phonemes was measured in milliseconds. Friedman test was used as the omnibus test with a level of significance set at α = 0.05, while Bonferroni-corrected Wilcoxon signed-rank test was used for pairwise comparisons. A total of 25 participants completed the follow-up. A statistically significant difference was found in the articulation of all plosive sounds among control, boil-and-bite mouthguard and custom-fitted mouthguard (P < .001). All pairwise comparisons were statistically significant (P < .001). Although the articulation of plosive sounds was distorted when boil-and-bite and custom-fitted mouthguards were used, distortions were more notable in the boil-and-bite mouthguard.